UNDERGROUND WATER ANALYSIS OF BUTIBORI AREA (NAGPUR) - Lalitkumar R. Turkar; Kalyani Raut; Arpit Mendhule; Kiran Bhange; Ravindra Kumari; Manisha Bodele; Prof. Mohitsingh Katoch (International Journal of Innovations in Engineering Research and Technology, 2021)
Water quality information is needed to assess the state of water contamination in a variety of community, including those that rely primarily on unimproved underground sources of drinking water. The study will be carried out to assess the quality of groundwater in particular sites of the domestic area of Butibori. The groundwater samples will be collected from a shallow well, tube well and bore wells located at specific places within the domestic area of Butibori. The research was focused on the physicochemical and bacteriological analysis of underground water from domestic sites.